Black Time in the Age of COVID: Improvising Afrologically in both Telematic Performance and Public Health Policy - Lewis, Eric (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Both telematic performances and COVID suffer from latency. In telematic performance, it is the lag between a musical gesture you make, and the time that others in the network receive it. In COVID, it is lags between contact and showing symptoms, and between public health policy decisions and their effects. I argue that we need to embrace latency as an improvisational partner both in our telematic performances, and in our health care policies. I argue that Black aesthetics and Black approaches to sound and improvisation have long embraced latency, and that we need to become what is sometime called Afro-logical improvisers both in our networked performances and in our COVID related health policies.